Rare Case of Meningoencephalitis by Listeria monocytogenes in a Young Immunocompetent Adult - Janette Alejandra Gamiño Gutierrez; Gustavo Adolfo Hernández Valdez; Arleth Anahí Montaño Gómez; Jorge Morales Rojas; Graciela Gaddy Robles Martinez; Anahi Herrera Ruelas; Alin Kaori Ferreyra Gudiño; Jocelin Celeste Jurado Cardona; Jimena Jexabeth Ibáñez Núñez; Anahí Fierros Ramos (Disease and Health Research: New Insights Vol. 6, 2024)
The aim of this paper is to consider L. monocytogenes as a possible atypical etiological agent of meningoencephalitis in patients without immunocompromise. Meningoencephalitis secondary to Listeria monocytogenes (L. monocytogenes) mainly affects newborns, the elderly, and immunocompromised people; there are extremely rare cases in which said infection occurs in immunocompetent individuals. The case of a young adult immunocompetent patient, with no known risk factors, who developed encephalitis, has been presented. The patient was treated with empirical antibiotic therapy, to which there was no response. Days later, a culture of the cerebrospinal fluid led to the diagnosis of Listeria monocytogenes infection. However, the patient died due to brain herniation. This case is exceptional, since it occurred in an individual outside the classic age group, in addition to not having risk factors, which is why it should be considered an atypical causal agent. Regimens without gentamicin may be preferable for patients who have impaired renal function or are taking other nephrotoxic drugs, such as cyclosporine.